Community engagement in the Transition movement: views and practices in Portuguese initiatives. Issue 12 (2nd December 2017) - Fernandes-Jesus, Maria; Carvalho, Anabela; Fernandes, Lúcia; Bento, Sofia
ABSTRACT: As the need to address climate change is ever more urgent, many have emphasised the importance of community-level responses. The Transition movement has advanced community-based action to increase resilience for over a decade and has expanded significantly. Thus, it is a critical setting for examining community engagement towards climate change in practice. Our study is based on 39 interviews with facilitators of Transition initiatives in Portugal, coupled with observational data, and is guided by two main research questions: how do Transition initiatives promote community engagement at the local level? What are the factors constraining or facilitating community engagement within Portuguese Transition initiatives? We identify several aspects of Transition's constructions of community resilience and engagement that indicate ambivalence towards, or avoidance of, certain issues. They relate do agency, structure, power and inclusion, as well as to the modes of engagement and the communication practices of Transition initiatives. We argue that strategies for community engagement should be specific to social contexts rather than internationally uniform and be based on participatory approaches. Drawing on an extensive empirical analysis, the article contributes to theory building on the Transition movement beyond the Anglo-Saxon context and to the wider field of community-based environment initiatives.